STUDIES ON CORRELATION AND PATH ANALYSIS FOR TRAITS RELATED TO WATER USE EFFICIENCY AND POD YIELD AND ITS COMPONENTS IN GROUNDNUT (ARACHIS HYPOGEA L.) - P. SHASHI KUMARA; B. G. SANJEEV; P. VENKATA RAVANA (The Bioscan, 2015)
Character association and path analysis among fourteen characters were studied in F 2 segregating generations of three groundnut crosses viz., KCG-6 × ICGV-91114, KCG-6 × TG-69 and TMV 2 × ICGV-00350. Analysis of correlation revealed that specific leaf area has significant negative correlation with SCMR(-0.59, -0.385, -0.70), total pods per plant (-0.59,-0.39, -0.70), matured pods per plant (-0.29, -0.25, -0.49), kernel yield (-0.36, -0.51, -0.06) and pod yield (-0.36, -0.18, -0.38). The pod yield was significantly positive correlated with SCMR(0.53, 0.50, 0.48), matured pods per plant (0.54, 0.67, 0.59), harvest index (0.38, 0.46, 0.69), kernel yield (0.83, 0.79, 0.89), oil yield (0.79, 0.76, 0.87) and sound mature kernel per cent (0.27, 0.37, 0.27). Path analysis indicated that, kernel yield per plant, matured pods per plant and sound mature kernel per cent showed highest direct effect on pod yield. This indicates that more emphasis can be given for following traits SCMR, matured pods per plant, kernel yield, sound mature kernel per cent and harvest index for the improvement of pod yield of groundnut.